THE EFFECT OF SPIRIT AT WORK, ORGANIZATIONAL CULTURE, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE PERCUT SEI TUAN CAMAT OFFICE - Slamet Widodo (Institute of Computer Science (IOCS), 2021)
This study aims to examine the effect of spirit at work, organizational culture, and work environment on the performance of civil servants at the Percut Sei Tuan Sub-district Office. The population in this study amounted to 30 employees with the entire population taken as research samples. Data collection was done by using the questionnaire method. The research data were analyzed quantitatively using multiple linear regression method with the help of SPSS 24.0 application. The results of the quantitative analysis show that the spirit at work, organizational culture, and work environment have a positive and significant effect on the performance of the Percut Sei Tuan Sub-District Office employees, either partially or simultaneously. Where partially the t-test shows that work enthusiasm has a tcount of 4.263 with a significance of 0.000, organizational culture has a t-count of 2.990 with a significance of 0.006, and the work environment has a t-count of 2.384 with a significance of 0.025 so that the most dominant variable affecting employee performance is the variable enthusiasm for work with the greatest count. Meanwhile, simultaneously with the F test shows that the resulting Fcount is 96.395 with a significant value of 0.000. The results of the determination test show that 90.8% of employee performance can be explained and obtained from the spirit, organizational culture, and work environment, while the rest is obtained from other factors. In which employee performance has a very strong relationship to the spirit, organizational culture, and work environment.